PERISTILAHAN DALAM ADAT PERKAWINAN DAYAK BAKATI PAYUT’N BENGKAYANG KAJIAN SEMANTIK - Rohani Rohani; Hotma Simanjuntak; Amriani Amir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractMarriage custom is a tradition or custom that is usually carried out by certain communities with regional uniqueness that is different from other regions. The custom of marriage is a cultural value that must be preserved and preserved and cannot be denied, as in the current era of globalization, the tradition of marriage has gradually begun to be abandoned by the community. The main focus that the author will examine is regarding the terms used in the traditional marriage procession, especially in the Dayak Bakati Payut'n community in Bengkayang Regency. The terms in the custom of the Dayak Bakati Payut'n marriage in Bengkayang Regency are very diverse, although they are rarely found. Data collection on terms in marriage customs is divided into three stages, namely pre-marriage, implementation of marriage and post-marriage. The method used in this research is descriptive method with qualitative research form. The techniques used in this research are observation, interview technique, fishing rod technique, face-to-face technique, note-taking technique and recording technique, while the tools used are questionnaires and documentation. Based on the results of the analysis, there are five classifications in the terms of the marriage custom of Dayak Bakati Payut'n Bengkayang semantic studies, namely based on the lexicon categories of rituals, cultural objects, actors, myths, processes.Keywords: Dayak Bakati, Terminology. Traditional Marriage.